Robust Angiogenesis and Arteriogenesis in the Skin of Diabetic Mice by Transient Delivery of Engineered VEGF and PDGF-BB Proteins in Fibrin Hydrogels - Certelli, Alessandro; Valente, Paolo; Uccelli, Andrea; Grosso, Andrea; Di Maggio, Nunzia; D’Amico, Rosalinda; Briquez, Priscilla S.; Hubbell, Jeffrey A.; Wolff, Thomas; Gürke, Lorenz; Mujagic, Edin; Gianni-Barrera, Roberto; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Non-healing ulcers are a serious complication of diabetes mellitus and a major unmet medical need. A major cause for the lack of healing is the impairment of spontaneous vascularization in the skin, despite mostly normal blood flow in deeper large vessels. Therefore, pro-angiogenic treatments are needed to increase therapeutic perfusion by recruiting new arterial connections (therapeutic arteriogenesis). Vascular endothelial growth factor (VEGF) is the master regulator of angiogenesis in physiology and disease, but exploitation of its therapeutic potential requires careful control of its dose distribution in tissue. Co-delivery of platelet derived growth factor-BB (PDGF-BB) has been shown to expand the therapeutic window of VEGF and also improve associated arteriogenesis. We used a highly controlled protein delivery system, based on a clinically applicable fibrin-based platform, to investigate the angiogenic and arteriogenic potential of engineered versions (TG-) of VEGF and PDGF-BB proteins in the skin of diabetic and obese db/db mice. Intradermal delivery of therapeutically relevant doses of TG-VEGF and TG-PDGF-BB induced robust growth of new microvascular networks with similar efficacy as in normal littermate control mice. Further, TG-PDGF-BB prevented the formation of aberrant vascular enlargements by high TG-VEGF levels. As fibrin was degraded after the first week, the induced angiogenesis mostly regressed by 4 weeks, but it promoted effective arteriogenesis in the dermal layer. Therefore, controlled co-delivery of TG-VEGF and TG-PDGF-BB recombinant proteins is effective to induce angiogenesis and arteriogenesis in diabetic mouse skin and should be further investigated to promote diabetic wound healing.